Co-based spinel pre-catalysts for water oxidation - Wu, Tianze (Nanyang Technological University, 2021)
To deal with the exhaustion of fossil fuels and the climate changes, extensive study has been carried out on electrochemical devices to produce hydrogen which is a clean and sustainable energy carrier. In these devices, the development of cost-effective electrode materials is essentially important. Special attention has been made on Co-based spinel oxides/sulfides. It has been found that some of them can undergo surface reconstruction under operando condition to evolve active sites toward alkaline OER. This also gives rise to the design of pre-catalysts which is aimed for specific reconstruction under operando condition for better activity. To gain a fundamental understanding of their reconstruction mechanisms is critical for mastering the reconstruction for better OER efficiency. This dissertation firstly points out a key electronic parameter, O 2p level relative to the Fermi level, closely associated to the reconstructability of spinel CoFexAl2-xO4. When the O 2p level is up lifted close to Fermi level, it will trigger the oxygen oxidation in the lattice. The resulted surface oxygen vacancies grant structural flexibility in oxides for reconstruction. Secondly, implied by a higher energy level of M-S state than M-O state, the spinel metal sulfide (e.g. CoFe2S4) is pointed out with higher reconstructability than its oxide counterpart (CoFe2O4). Moreover, by investigating the chemistry of the reconstructed species of CoFe2S4, ferromagnetic Fe-S components were found, which is critical for the spin transfer and charge conductivity throughout the reconstructed oxyhydroxides. Thirdly, the ways to evolve oxyhydroxide layer with limited thickness is essential for controlling the reconstruction.